Indicators related to physical disability and diagnosis of leprosy - Leano, Heloisy Alves de Medeiros (2018)
Objective: to analyze the trend of epidemiological indicators of leprosy related to diagnosis and physical disability. Methods: ecological study of time series. The secondary data were extracted from the Brazilian Notifiable Diseases Information System. Prais-Winsten generalized linear analysis was used for trend analysis. Results: 240,028 new cases of leprosy were analyzed. The Northeast region showed a decreasing annual trend (-2.9%) for general detection. As for disability, there are differences among the states of Bahia (4.9%), Alagoas (4.1%), Piauí (2.5%), Maranhão (2.2%) and Ceará (2.1%), which presented increasing trend to grade 2 ratio in the general population. Bahia (9.5%), Sergipe (6.6%) and Maranhão (4.9%) also presented an increasing trend to grade 2 among children. Conclusion:the Northeast region has remained at a very high endemicity level for leprosy with a difference in the distribution of the disease among the states. It was shown active transmission of the bacillus, late diagnosis and underreporting in the region.